2022
DOI: 10.1177/20552076221131144
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of information communication technology-based health information services: Exploring the culture in primary-level health care of South Ethiopia, using Utaut Model, Ethnographic Study

Abstract: Introduction In sub-Saharan African countries including Ethiopia, the acceptance of Information Communication Technology (ICT) in health is at the proof-of-concept level with a few unsustainable piecemeal of pilot projects. Thus, a desirable willingness of acceptance among healthcare providers is a paramount. Material and Methods Eight months elapsed ethnographic study design was conducted using participant observation and key informant interviews. The data were entered on Qualitative Data Analysis mine softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In the final systematic review, ten studies from Ethiopia were included. In all eight studies, except one mixed-method [ 31 ] and one qualitative study [ 32 ], nine cross-sectional quantitative design study was included. Seven of these studies among healthcare professionals, one done on the student [ 33 ], one among reproductive healthy women [ 21 ], and one among DM patients were conducted [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the final systematic review, ten studies from Ethiopia were included. In all eight studies, except one mixed-method [ 31 ] and one qualitative study [ 32 ], nine cross-sectional quantitative design study was included. Seven of these studies among healthcare professionals, one done on the student [ 33 ], one among reproductive healthy women [ 21 ], and one among DM patients were conducted [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study finding revealed that participants who were grouped young age (10.0%) [ 21 ], secondary and above educational level (10.0%) [ 21 ], perceived enjoyment (10.0%) [ 33 ], favorable attitude (30.0%) [ 3 , 17 , 35 ] and good habit (10.0%) [ 18 ] frequently occurred in studies and the individual facilitators of sustainable acceptance of e-health systems in Ethiopia. Whereas anxiety(fear of new technologies) appeared in 2 studies (20.0%) [ 8 , 32 ]. In addition, older age, lack of interest to use, perceived as systems are not save time and money, unable to share knowledge, and had not experienced work were the individual barriers to sustainable acceptance of e-health systems in our study, which occurred once from the study (10%) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Egypt, the e-learning system implemented was with high acceptance level(18). In Developing countries, recent study indicates that the magnitude of intention to use e-learning system in higher education institutions is low (19)(20)(21). In Ethiopia, recent study indicate that the magnitude of intention to use e-learning system in higher education institutions is low (19%) in the case of teachers (22).…”
Section: Introductionmentioning
confidence: 99%